Electrochemical production of hydrogen and lithium hydroxide under defined flow conditions
By using LiSICon film to perform membrane electrolysis in electrochemical batteries, the problem of efficient separation of lithium recovery from waste lithium ion battery packs and economical production of lithium hydroxide is solved, and efficient and economical lithium recycling and lithium hydroxide production is achieved, extending the service life of the membrane.
Patent Information
- Application Number
- CN202380065507.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-12
- Filing Date
- 2023-09-11
- Publication Date
- 2025-05-06
AI Technical Summary
In the prior art, when recovering lithium from waste lithium ion battery packs, it is difficult to achieve efficient separation and economical production of lithium hydroxide. In addition, the LiSICon film is sensitive to impurities, has a short service life, and high costs lead to uneconomical recycling.
The electrochemical cell using LiSICon film is used to perform membrane electrolysis, and Li cations are driven through the membrane by voltage, thereby enriching lithium hydroxide in the cathode compartment of the electrochemical cell, and improving the permeability and service life of the membrane by controlling the cross-flow velocity and flow conditions.
The economical production of lithium hydroxide on an industrial scale is achieved, the energy efficiency is improved, and the service life of the film is extended. Even if the feed contains impurities that are harmful to LiSICon materials, it can maintain high efficiency.
Smart Images

Figure CN119947990A_ABST
Abstract
Description
[0001] For the production of lithium-ion batteries (LIBs), lithium (Li) is by definition necessary. Due to its high reactivity, lithium does not exist in pure form in nature, but always in bound form. The starting materials for the production of LIBs are generally lithium hydroxide (LiOH) or lithium carbonate (Li 2 CO 3 ) form of lithium.
[0002] In most natural deposits, Li is present as lithium oxide (Li 2 O) or lithium sulfate (Li 2 SO 4 ) or lithium chloride (LiCl). Lithium oxide is a component of ores such as pegmatites, while lithium sulfate and lithium chloride are present in dissolved form in the leachate of Li salt lakes. During mining, the lithium compounds extracted in certain cases are converted into lithium carbonate (Li 2 CO 3 ). In a further process step, lithium carbonate can be converted into lithium hydroxide by reaction with quicklime or calcium hydroxide. The extraction of Li and its conversion into LiOH are described in:
[0003] Wietelmann, U. and Steinbild, M. (2014). Lithium and Lithium Compounds. In Ullmann's Encyclopedia of Industrial Chemistry, (ed.). DOI: 10.1002 / 14356007.a15_393.pub2.
[0004] Rich lithium deposits are known to exist, but producing LiOH from the lithium compounds they contain is energy-intensive and produces large amounts of wastewater. Also, there is a strategic need to break away from dependence on the owners of the deposits.
[0005] One solution to this problem could be to reprocess the material from spent LIBs so that the lithium contained therein can be reused as raw material for new batteries.
[0006] Recovery methods for LIBs have been developed to industrial maturity in the past, but in most cases for the metals Fe, Ni, Mn, Co, Mg and Al present therein. The alkali metal Li is generally not recovered because its high reactivity makes it difficult to separate from spent batteries and it is available in sufficient quantities from natural deposits at low cost. For a long time, it seemed that the extraction of Li from spent LIBs was not economical at all.
[0007] However, there is now increasing social and economic pressure to recover lithium from used LIBs. To achieve this, it is necessary to supply LIB producers with recycled Li in an acceptable quality so that the method for making LIBs from recycled Li is no different from the method for making LIBs using mined virgin Li. It goes without saying that there must be no adverse effect on the quality of the battery pack. Therefore, the recycled Li, especially the recycled Li in the form of LiOH, must meet very strict purity specifications. In addition, the method for recovering Li from old batteries must be as energy efficient as possible. The method should also use very little water.
[0008] Known methods for recovering lithium from old batteries are summarized in the following document:
[0009] Pankaj K.Choubey et al.:Advance review on the exploitation of the prominent energy-storage element Lithium.Part II:From sea water and spentlithium ion batteries(LIBs),Minerals Engineering,volume 110,2017,pages 104-121
[0010] DOI:10.1016 / j.mineng.2017.04.008.
[0011] A technology which is mentioned only in passing as “LISM” in the aforementioned review article is the electrolysis of Li-containing water by means of so-called LiSICon membranes.
[0012] LiSICon stands for lithium superionic conductor. This is a class of inorganic, (glass-) ceramic materials that are electrically insulating but at the same time intrinsically conductive for Li ions. The transport mechanism for Li derives from the crystal structure of the material. In short, the Li ions "pass through" the crystal. Commercially available LiSICon materials include lithium aluminum titanium phosphate (LATP), lithium aluminum titanium silicon phosphate (LATSP), lithium aluminum germanium phosphate (LAGP) and lithium lanthanum titanium oxide (LLTO). These materials were originally developed as solid-state electrolytes for LIBs. An overview of the transport mechanism of LiSICon, their crystal structure and production is given in the following literature:
[0013] Palakkathodi Kammampata et al.: Cruising in ceramics–discovering new structures for all-solid-state batteries–fundamentals, materials, and performances. Ionics 24, 639-660 (2018)
[0014] DOI: 10.1007 / s11581-017-2372-7
[0015] Yedukondalu Meesala et al.: Recent Advancements in Li-Ion Conductors for All-Solid-State Li-Ion Batteries. ACS Energy Lett. 2017, 2, 12, 2734-2751
[0016] DOI: 10.1021 / acsenergylett.7b00849
[0017] The following literature describes specific LiSICon stoichiometry:
[0018] Sofia Saffirio et al. Li 1.4 Al 0.4 Ge 0.4 Ti 1.4 (PO 4 ) 3 promising NASICON-structured glass-ceramic electrolyte for all-solid-state Li-based batteries: Unravelling the effect of diboron trioxide, Journal of the European Ceramic Society, volume 42, issue 3, 2022, pages 1023-1032 DOI 10.1016 / j.jeurceramsoc.2021.11.014。
[0019] Eongyu Yi et al.Materials that can replace liquid electrolytes in Libatteries:Superionic conductivities in Li 1.7 Al 0.3 Ti 1.7 Si 0.4 P 2.6 O 12 .Processingcombustion synthesized nanopowders to free standing thin films. Journal of Power Sources, volume 269, 2014, pages 577-588, DOI 10.1016 / j.jpowsour.2014.07.029.
[0020] The selective conduction of Li ions by LiSICon materials means that LiSICon materials can be used as membranes for separating Li from Li-containing mixtures. Li must be present in the mixture in ionic form, for example as a Li salt dissolved in water. The driving force required to push the Li ions through the LiSICon membrane is voltage. For this purpose, an electrochemical cell is constructed, which includes two electrodes and a LiSICon membrane that divides the cell into two compartments. There are electrodes in each compartment. Depending on the polarity of the electrodes present in each compartment, the compartment is called anode or cathode. Voltage is applied to the electrodes and the anion compartment is filled with Li-containing water as anolyte. The cathode compartment is filled with water as catholyte. The membrane allows Li cations to pass through to the cathode. As a result, the water in the cathode compartment (catholyte) becomes rich in Li, while the Li in the water on the anode side (anolyte) is reduced. Such a method is called membrane electrolysis.
[0021] Membrane electrolysis processes for extracting lithium by means of LiSICon membranes have been described in the prior art.
[0022] For example, Zhen Li et al. describe a method using weakly lithium-bearing water from the Red Sea as a raw material:
[0023] Zhen Li et al.: Continuous electrical pumping membrane process for seawater lithium mining. Energy Environ. Sci., 2021, 14, 3152 DOI: 10.1039 / d1ee00354b.
[0024] Zhen Li's research group used LLTO as a membrane. The target product separated was lithium phosphate (Li 3 PO 4 ), which is suitable for producing lithium iron phosphate (LFP) battery packs. It cannot be directly used to produce LIBs with different cathode materials, such as nickel-manganese-cobalt (NMC) or lithium manganese oxide (NMO).
[0025] Yang et al. attempted to extract metallic lithium directly from seawater using solar energy, LAGP membrane and copper foil.
[0026] Sixie Yang et al.: Lithium Metal Extraction from Seawater. Joule, volume2, issue 9, 2018, pages 1648-1651, DOI 10.1016 / j.joule.2018.07.006.
[0027] US 2016 / 0201163 A1 describes the separation of Li ions from salt water such as seawater by means of a LiSICon membrane. The membrane material proposed is specifically Li 3 N.Li 10 G 2 S 12 ,La x Li y TiO 2 and Li 1+x+y Al x (Ti,Ge) 2-x Si y P 3-y O 12 The target product is lithium carbonate (Li 2 CO 3 ).
[0028] WO 2019055730 A1 also relates to the separation of lithium by means of a LiSICon membrane. LLTO, LAGP and LATP are specifically mentioned. The LiSICon material can be applied to a support structure. The chemical properties of the support structure are not described in detail. Likewise, there is little description of how to implement the application of LiSICon to the support structure. The target product separated is Li ions.
[0029] US9222148B2 also discloses the electrolytic separation of lithium hydroxide on a LiSICon membrane and the subsequent precipitation of lithium hydroxide hydrate.
[0030] In addition to the use of ceramic LiSICon membranes, electrolytic processes for lithium separation using organic ion exchange membranes are also known.
[0031] For example, EP 3805428 A1 describes the electrolytic production of lithium hydroxide. In addition to the electrolysis, an electrochemical conversion of lithium into lithium hydroxide is also carried out. In order to obtain the necessary reactants, water undergoes a simultaneous electrochemical decomposition. This is carried out using a bipolar three-compartment cell with an ion exchange membrane. Commercially available AVV, 902, FAB, FKB and CMB ion exchange membranes. The chemical nature of these ion exchange membranes is not disclosed in EP 3805428 A1, but they will most likely be organic membrane materials. The three-compartment cell operates in an acidic medium. In particular, a feedstock containing, for example, lithium sulfate (Li 2 SO 4 ) or water of a Li salt of lithium chloride (LiCl). The volume flow rate and gap size through the example cell are specified, but the width of the cell is not specified. The flow internals in the cell are not mentioned.
[0032] US 10036094 B2 discloses the production of lithium hydroxide by two-stage electrolysis of aqueous lithium sulfate and / or lithium hydrogen sulfate solutions with simultaneous water decomposition. The first stage uses an electrochemical cell with two compartments, and the second stage uses a three-compartment cell. The prevailing pH in the three-compartment cell can be 8 to 10. The cell is equipped with an ion exchange membrane. The chemical composition of the ion exchange membrane is not given. The following commercial membranes are mentioned: FAB, ACM, MV, 324 and AHA.
[0033] The main disadvantage of polymer membranes is their permeability to water. This results in dilution of the anolyte with water from the catholyte. In addition, organic ion exchange membranes have lower ion selectivity than inorganic LiSICon materials. They not only allow Li + By, and allow Na + In addition to the purity of the target product, the electrical efficiency of the process is also affected: if non-ion selective membranes are used for electrolysis, the unwanted Na + The transmission to the second compartment will also consume precious energy. In addition, when reaching the second compartment, Na + The undesired electrochemical processes will convert the electrolyte into unwanted byproducts. Based on the yield of the target product Li, the energy efficiency of the process is reduced. Finally, these membranes are sensitive to divalent cations such as Mg. ++ and Ca ++Over time, these cations poison the membrane, limiting the useful life of organic ion exchange membranes.
[0034] Glass-ceramic LiSICon materials ensure better ion selectivity. However, the stability of LiSICon membranes towards impurities remains a highly significant problem for industrial practice. For example, Li-containing + Water contains other cations, especially such as Na + and K + , which causes lasting damage to the LiSICon material: These cations appear to occupy defects in the crystal structure, making the Li + The transport of cations through the membrane virtually stops. The service life of the electrochemical cell then expires. The high cost of the LiSICon material means that it is uneconomical to recover Li from LIBs if the membrane has a short service life. In addition, the brine from the Li salt lakes has a naturally high sodium content and is therefore not suitable for contact with known LiSICon membranes. Therefore, the lithium from the salt lakes also undergoes an energy-intensive thermal separation process and / or a stepwise process using large amounts of water, in which the lithium is dissolved and then recrystallized. While the water here can be evaporated by solar radiation, water for dissolving LiCl is scarce in the deserts of South America. Therefore, this route is very difficult there.
[0035] Another practical problem is the high specific resistance of the LiSICon material. This results in an electrochemical cell with a high ohmic internal resistance, which means that the process has a correspondingly high electrical energy requirement. In order to reduce this, the membrane could theoretically be made thinner. However, the low thickness of the material results in only a short life in aggressive environments.
[0036] Based on all the above, the problem addressed by the present invention is to provide a Li-containing + A process for the electrochemical production of LiOH from water which can also be operated economically on an industrial scale. In particular, the process should have good energy efficiency and achieve long membrane lifetimes even when the feed employed contains impurities which are harmful to the LiSICon material.
[0037] This problem is solved by a method for producing hydrogen and lithium hydroxide, comprising the following steps:
[0038] a) providing a feed comprising at least water, Li ions and impurities, wherein the concentration of Li ions in the feed is C F at least 200 ppm by weight or between 500 ppm by weight and 140 000 ppm by weight, in each case based on the total weight of the feed,
[0039] b) providing a lean working medium comprising water and lithium hydroxide dissolved therein, wherein the concentration of lithium hydroxide in the lean working medium is C based on the total weight of the lean working medium. M0 At least 50 ppm by weight;
[0040] c) providing at least one electrochemical cell, wherein the electrochemical cell has the following characteristics:
[0041] i. The electrochemical cell comprises a first compartment in which an anode is arranged;
[0042] ii. The electrochemical cell comprises a second compartment in which a cathode is disposed;
[0043] iii. The electrochemical cell comprises a flat membrane separating the first compartment from the second compartment, the
[0044] The flat membrane has an area A;
[0045] iv. The flat membrane comprises an inorganic material having Li ion conductivity and being electrically insulating;
[0046] d) providing at least one voltage source connected to the anode via a first electrical lead and to the cathode via a second electrical lead;
[0047] e) continuously filling the first compartment with the feed;
[0048] f) filling the second compartment with the lean working medium;
[0049] g) charging the electrochemical cell with a voltage U taken from the voltage source so that a current I flows between the anode and the cathode, and a ratio Q of the current intensity of the current I to the area A of the flat membrane is between 100 A / m 2 and 500A / m 2 Between or 150A / m 2 and 350A / m 2 between;
[0050] h) continuously taking out wastewater containing at least water, Li salt dissolved therein, oxygen and impurities from the first compartment, wherein the concentration of Li ions in the wastewater is C based on the total weight of the wastewater. W Lower than the concentration of Li ions in the feed C F ;
[0051] i) taking out a rich working medium containing water, lithium hydroxide and hydrogen from the second compartment, wherein the concentration of lithium hydroxide in the rich working medium is C based on the total weight of the rich working medium. M1 Greater than the concentration C of lithium hydroxide in the lean working medium M0 ,
[0052] Wherein, due to the continuous filling of the first compartment with the feed and the continuous withdrawal of wastewater from the first compartment, a first flow is formed, and the first flow flows through the first compartment along the flat membrane at a crossflow velocity CFV, and the crossflow velocity CFV is greater than 220 mm / s or greater than 350 mm / s or greater than 470 mm / s.
[0053] A key aspect of the present invention is to establish flow conditions in the first compartment of the electrochemical cell such that the anolyte flows along the membrane with a certain minimum cross-flow velocity.
[0054] The anolyte is the material in the first compartment. The inflow is the feed and the outflow of the first compartment is the wastewater. In the first compartment, the anolyte is converted from the feed to the wastewater by an electrochemical process in the cell.
[0055] The cross-flow velocity (CFV) is an operating parameter established by membrane technology. It is calculated from the ratio of the volume flow Q through the first compartment to the flow cross section of the first compartment (i.e. the product of the width b of the membrane perpendicular to the flow direction and the height h of the gap between the membrane and the anode):
[0056] CFV=Q / (b*h)
[0057] According to the understanding of this case, the cross flow velocity CFV should be greater than 220 mm / s. It is better that the cross flow velocity CFV is greater than 350 mm / s, and it is also better that the cross flow velocity CFV is greater than 470 mm / s.
[0058] A high cross-flow velocity can have the effect that impurities present in the anolyte originating from the feed precipitate to a lesser extent on the membrane and are flushed out of the first compartment again together with the wastewater. This means that the impurities do not clog the membrane, thereby reducing its permeance.
[0059] Experimental data confirm that the permeability of the membrane increases with increasing cross-flow velocity. The permeability indicates how much mass of lithium is transported through the membrane per unit membrane area and per unit time. The permeability is therefore a measure of the efficiency of the process. Therefore, it is expected that at higher cross-flow velocities, the profitability of the process increases.
[0060] The cross-flow velocity cannot be increased to infinitely high levels because increased turbulence will be created in the flow, which increases the flow resistance. As a result, increased drive power is required to pump the anolyte through the first compartment.
[0061] In order to achieve a good compromise between the achieved permeability and the applied driving performance, it makes sense to limit the cross flow velocity. Therefore, the cross flow velocity CFV should be lower than the limit velocity. The achievable limit velocity depends on the configuration of the electrochemical cell and its auxiliary units and can be, for example, 600 mm / s or 960 mm / s or 1500 mm / s or 2400 mm / s or 3780 mm / s or 6000 mm / s.
[0062] It has surprisingly been found that flow internals such as spacers as fitted in spiral wound modules can have a negative impact on the permeability of the process. This is surprising since spacers are often used in membrane processes. Therefore, in a preferred development of the invention, flow internals such as spacers are omitted.
[0063] According to the invention, flat sheet membranes are used. It has not been possible to realize electrochemical cells with hollow fiber membranes so far.
[0064] Flat-plate membranes are preferably used in flat-plate modules. Use in spiral-wound modules is disadvantageous because wiring has proven to be complicated here. In addition, flow control in spiral-wound modules has been found to be problematic because in electrolysis both half-cells must be filled with electrolyte or have electrolyte flowing through them: for gas separations, which are usually operated in spiral-wound modules, only the permeate needs to be removed.
[0065] This is advantageous when a flow is formed not only through the first compartment but also through the second compartment. Therefore, in a further embodiment of the invention, the charging of the lean working medium into the second compartment and the removal of the rich working medium from the second compartment occur continuously, as a result of which a second flow is formed through the second compartment.
[0066] The flow conditions in the second compartment are preferably set so that the working medium (catholyte) exhibits a laminar flow.The second compartment then has a low flow resistance, as a result of which less energy is required to transport the working medium.
[0067] Due to the flow conditions prevailing in the cell, the feed may contain impurities which are generally harmful to the lithium conducting membrane material. More particularly, the defined flow conditions at the membrane make it possible to operate with feeds containing one or more of the following anions: sulfate, carbonate, hydroxide and chloride.
[0068] In addition to the anions mentioned, the feed may also contain impurities in the form of compounds of the following elements: B, Na, Mg, Al, Si, K, Ca, Mn, Fe, Co, Ni, Cu, C. The alkali metals and alkaline earth metals listed are elements found together with lithium in natural deposits, while the other metals mentioned are used as electrical conductors or cathode materials in LIBs and are therefore present in the feed obtained from the reprocessing of used LIBs. The carbon originates from organic materials used in LIBs, such as films, separators, adhesives or sealants.
[0069] According to the invention, a membrane comprising an inorganic material is used. Thus, the desired ion selectivity is achieved differently from the case of polymer membranes. The membrane preferably consists entirely of inorganic material. Composite membranes, which contain only inorganic material as a coating on a support material or in which the inorganic material is dispersed in different types of matrix materials, have proven to be a wrong approach.
[0070] The advantage of inorganic membranes over polymer membranes also lies in their mechanical stiffness: thus, at higher cross-flow velocities, inorganic membranes do not oscillate as much as polymer membranes.
[0071] In order for this method to work, the inorganic material must conduct Li ions and at the same time act as an electrical insulator.
[0072] The specific conductivity σ for Li ions should be at least 1×10 -5 S / m or at least 5×10 -5 S / m or at least 10×10 -5 S / m, and not more than 100×10 -5 S / m. The Li conductivity of the material was measured by impedance spectroscopy. The measurement was performed as follows:
[0073] The measuring device comprises two cylindrical electrodes, with the sample arranged between them. In order to ensure optimal contact with the electrodes and a reproducible contact pressure, a weight is placed on the sample.
[0074] A potentiostat (Zahner-Elektrik I. Zahner-Schiller GmbH & Co. KG, Kronach-Gundelsdorf, Germany) was connected to the electrodes and controlled via Thales software (Zahner). Measurements were performed in the frequency range of 1 Hz to 4 MHz and at an amplitude of 5 mV using samples that had been polished and sputtered on a thin conductive gold layer.
[0075] The measurement results are presented in the form of Nyquist plots and evaluated using analysis software (Zahner). The resistance is read at the maximum of the Nyquist plot curve. The formula σ = (h·10 4 ) / (R·π / 4·d 2 ) to calculate the specific ionic conductivity σ [mS / cm], where h is the sample height in mm, R is the measured resistance in Ω, and d is the sample diameter in mm.
[0076] The specific conductivity of electrons γ (conductivity) should be less than 10 at 23°C. -7 S / cm(10 -9 S / m) or less than 10 -12 S / m or less than 10 -16 S / m. From the point of view of electron conduction, inorganic materials are therefore classified as non-conductors.
[0077] LiSICon is preferably used as inorganic material. LiSICon materials are glass-ceramic substances that conduct lithium ions and at the same time act as electrical insulators. For the purposes of the present invention, all known LiSICon materials can in principle be used as inorganic materials. Known LiSICon materials meet the requirements specified above for conductivity and ion conductivity of inorganic materials.
[0078] For example, the material LiSICon lithium aluminum titanium phosphate (LATP) may be used. Thus, in one variant of the invention, the inorganic material is a compound having the following stoichiometry:
[0079] Li 1+x Al x Ti 2-x (PO 4 ) 3
[0080] Wherein: 0.1≤x≤0.3, wherein preferably x=0.3.
[0081] Alternatively, the LiSICon material lithium aluminum germanium phosphate (LAGP) can be used. Thus, in one variant of the invention, the inorganic material is a compound of the following stoichiometry:
[0082] Li 1+x Al x Ge 2-x (PO 4 ) 3
[0083] Where: x=0 or x=0.2 or x=0.4.
[0084] Alternatively, the LiSICon material lithium aluminum titanium silicon phosphate (LATSP) can be used. Thus, in one variant of the invention, the inorganic material is a compound with the following stoichiometry:
[0085] Li 1+x+y Al x Ti 2-x Si y P 3-y O 12
[0086] Among them: 0.1≤x≤0.3, and 0.2≤y≤0.4.
[0087] However, particular preference is given to using LiSICon which is derived from lithium aluminium germanium phosphate but which additionally contains titanium. This is known as LAGTP.
[0088] Thus, in a preferred variant of the invention, the inorganic material is a compound of the following stoichiometry:
[0089] Li 1.4 Al 0.4 (Ge 1-x Ti x ) 1.6 (PO 4 ) 3
[0090] Among them: 0≤x≤1.
[0091] In a particularly preferred development of the invention, LATSP is used which additionally contains germanium. This is known as LAGTSP.
[0092] Thus, in a particularly preferred variant of the invention, the inorganic material is a compound of the following stoichiometry:
[0093] Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 *nGeO 2
[0094] Among them: 0≤x≤1, 0≤y≤1, and 0≤n≤1.
[0095] LAGTSP is available, for example, from Ohara GmbH, Hofheim, Germany under the product name AG01 obtained.
[0096] As an alternative to the phosphates mentioned, the oxidic LiSICon material lithium lanthanum titanium oxide (LLTO) can be used. Thus, in one variant of the invention, the inorganic material is a compound with the following stoichiometry:
[0097] Li 3x La (2 / 3)-x□(1 / 3)-2x TiO 3
[0098] Where: 0≤x≤0.16.
[0099] The lithium hydroxide is present in the rich working medium and is taken out of the second compartment together with the lithium hydroxide. In order to be able to utilize the lithium hydroxide, it is necessary to separate it from the rich working medium. A separation device is provided for this purpose. Therefore, a preferred development of the present invention comprises the following additional method steps:
[0100] k) providing separation equipment;
[0101] 1) Separating lithium hydroxide from the rich working medium by means of the separation device.
[0102] After separation of lithium hydroxide from the rich working medium, the working medium can be disposed of as wastewater or preferably reused as lean working medium. To this end, the separation device must be operated so that the LiOH is not completely separated, but maintained at a specified minimum concentration c of 50 ppm LiOH. m0 This allows the working medium to be recycled to the second compartment as lean working medium. This then results in recycling of the working medium between the second compartment and the separation device.
[0103] Therefore, a preferred development of the invention comprises the following additional method steps:
[0104] 1) separating lithium hydroxide from the rich working medium by means of a separation device to obtain a lean working medium,
[0105] The steps
[0106] b) providing a lean working medium comprising water and lithium hydroxide dissolved therein, wherein the concentration of lithium hydroxide in the lean working medium is C based on the total weight of the lean working medium. M0 At least 50 ppm by weight;
[0107] With the help of separation equipment.
[0108] In order to make it possible to recirculate the working medium between the separation device and the second compartment, it makes sense to install both devices at the same location. The same location is to be understood as meaning an integrated production facility. The electrochemical cell and the separation device are therefore part of an integrated facility.
[0109] It is also conceivable that the separation device is located at a different location away from the electrochemical cell. In this case, however, the working medium must be transported between the cell and the separation device. However, from an energy point of view, this is of little significance.
[0110] Preferably, at least the electrochemical cell is operated continuously on the anolyte side and the cathode side. This means that loading the lean working medium into the second compartment and removing the rich working medium from the second compartment occur continuously, with the result that a second flow through the second compartment is generated. Therefore, there is a constant flow in the two compartments. The first compartment has a continuous flow of feed, resulting in the production of wastewater, while the second compartment has a flow of working medium, which flows in as a lean working medium and flows out as a rich working medium. This makes it possible to achieve both a higher throughput and to continuously remove the components that damage the membrane in the feed and the working medium. Therefore, continuous operation can be expected to achieve better membrane stability than in intermittent operation on the cathode side.
[0111] In continuous operation, care must also be taken to ensure that the anolyte flow conditions according to the invention are maintained, that is, the first stream passes along the membrane through the first compartment at a sufficiently high cross-flow velocity. However, with regard to the catholyte flow conditions in the second compartment, the aim should be to achieve laminar flow, as this reduces the flow resistance in the second compartment, meaning that less energy is required to move the working medium. Therefore, in a particular embodiment, the second stream is laminar flow. BRIEF DESCRIPTION OF THE DRAWINGS
[0112] The present invention will now be described in detail with reference to the process flow diagram. In this regard, the accompanying drawings show:
[0113] Figure 1 :Simultaneous Li + Functional principles of membrane electrolysis and water electrolysis;
[0114] Figure 2 : Shows the functional principle of the recirculation between the electrochemical cell and the separation device.
[0115] The electrochemical cell 0 required to carry out the method is shown in Figure 1 It comprises a first compartment 1 and a second compartment 2. The two compartments 1 and 2 are separated from each other by a membrane 3. Arranged in the first compartment 1 is an anode 4. Arranged in the second compartment 2 is a cathode 5. Therefore, the first compartment 1 can be called an anode compartment and the second compartment 2 can be called a cathode compartment.
[0116] A first electrical lead 6 connects the anode 4 to a voltage source 7. A second electrical lead 8 connects the cathode 5 to the voltage source 7. The selected polarity of the voltage source 7 is such that the positive pole of the voltage source 7 is connected to the anode 4 and the negative pole of the voltage source 7 is connected to the cathode 5.
[0117] The electric current I flows through the two electrical leads 6 and 8 and through the voltage source 7. Since the membrane 3 acts as an electrical insulator, there is no electrical short circuit between the two electrodes 4 and 5 through the membrane 3.
[0118] The membrane 3 is a flat plate membrane consisting entirely of LiSICon material. The anode 4 is a metal flat plate containing titanium, niobium or tantalum. The cathode 5 is likewise a metal flat plate containing titanium or nickel. In the simplest case, a stainless steel plate is used as cathode. The anode 4, cathode 5 and membrane 3 have the same shape and can be rectangular or circular. Figure 1 This is not obvious from the side view of the electrode. Expanded metals, grids or meshes of specific materials can also be used instead of metal plates as electrodes.
[0119] The electrochemical cell 0 has an active area A which corresponds substantially to the surface area of the membrane 3, the anode 4 and the cathode 5. By installing sealing elements, the active area can be reduced relative to the actual area of the electrodes and the membrane. The active area is the proportion of the area of the cell 0 that is available for electrochemical processes.
[0120] During operation, the first compartment 1 is filled with a feed 10. The feed 10 is a Li + From an electrochemical point of view, the feed 10 can be considered as an anolyte.
[0121] The feed 10 may be a Li leachate from a natural ore deposit or a material stream generated by processing spent LIBs. Based on the total mass of the feed, the Li content of the feed 10 is + The concentration of cations (the formula symbol is c F ) should be at least 200 wt ppm. Seawater has a lower Li concentration and therefore must first be concentrated before it is used in the process. Feed 10 also contains anions, such as sulfate or chloride. Feed 10 also contains impurities. Anions and impurities are not shown in FIG. Figure 1 The main component of feed 10 is water H 2 O.
[0122] The second compartment is filled with a lean working medium 12. The lean working medium 12 is a medium having a low concentration of C M0 Li + Cationic water H 2 O. Based on the total mass of the lean working medium 12, the concentration c M0 From an electrochemical point of view, the lean working medium 12 can be considered as a catholyte.
[0123] The electrochemical cell 0 is also charged with a voltage U taken from the voltage source 7. This has the following effects:
[0124] First, water electrolysis occurs, where water (H 2 O) is electrochemically decomposed into hydrogen (H 2 ) and oxygen (O 2 ). At the cathode 5, OH is formed - and hydrogen. However, OH - The anions cannot pass through the membrane 3 and interact with the Li + The cations combine to form lithium hydroxide (LiOH). At the anode 4, oxygen and H + .
[0125] The Li from feed 10 is driven by voltage U + The cations migrate to the cathode 5 to maintain the formation of LiOH in the cathode compartment 2. They pass through the membrane 3 by virtue of the Li ion conductivity of the membrane and accumulate in the working medium (membrane electrolysis). This results in the formation of a rich working medium 13, which is discharged from the second compartment 2. The Li in the rich working medium 13 + The concentration of ions is greater than that in the lean working medium 12, so c M1 >c M0 .
[0126] Therefore, water electrolysis, Li + The membrane electrolysis and LiOH synthesis are carried out simultaneously in the electrochemical cell 0.
[0127] Therefore, the simultaneous operation of Li+ membrane electrolysis and water electrolysis in an electrochemical cell leads to the direct formation of lithium hydroxide LiOH and molecular hydrogen H 2 LiOH dissolves in water. Part of the hydrogen is dissolved and part exists in gaseous form. 2 The water is taken out from the cathode compartment of the cell as the rich working medium 13. Similarly, the gaseous hydrogen H is taken out from the second compartment 2. 2 .
[0128] Due to membrane electrolysis, the feed of 10 Li + is reduced, producing wastewater 14. Therefore, c W <c F Here, the formula symbol c W represents the concentration of Li ions in the wastewater 14 based on the total mass of the wastewater 14. Here, the formula symbol c F represents the concentration of Li ions in the feed 10 based on the total mass of the feed 10.
[0129] Figure 1 It is also shown how to determine the cross-flow velocity CFV. This involves measuring the distance between the membrane 3 and the anode 4, i.e. the height h of the gap. In addition, the width b of the membrane 3 is measured perpendicular to the flow direction. The width b is Figure 1The volume flow Q of the anolyte through the first compartment is then determined.
[0130] Then, the cross-flow velocity CFV can be determined as
[0131] CFV = Q / (b*h).
[0132] If the flat membrane used is not rectangular, the average width must be used. When using circular cells / membranes, the width b is taken as the maximum width of the channel cross section. 1 / 2 √2 (about 70%). The maximum width of the channel cross section is the diameter of the active area A. Therefore, for a circular flat membrane with diameter D, the width b is equal to the side length of a square whose perimeter is the diameter D of the circular active area A of the cell. Therefore,
[0133] b= 1 / 2 √2*D.
[0134] Figure 2 Depicts how LiOH is extracted as target product 15 from the rich working medium 13 .
[0135] For this purpose, a separation device 16 is provided, into which the rich working medium 13 is fed. The separation device 16 separates a target product 15, which has a particularly high concentration of LiOH, from the rich working medium 13. The target product also contains water and impurities, depending on the desired specifications of the target product.
[0136] The separation device 16 may be a distillation column or a crystallizer.
[0137] The LiOH-depleted output stream from the separation device 16 is recycled as lean working medium 12 to the second compartment 2 of the electrochemical cell 0 .
[0138] As mentioned previously, the lean working medium 12 needs to have a certain LiOH concentration C M0 , so that the process in the electrochemical cell 0 can be started in a desired manner with a low starting resistance. Based on the total mass of the lean working medium 12, the concentration c M0 Should be at least 50 ppm by weight. To ensure the required concentration C M0 , the separation device 16 is operated so that not all LiOH is separated from the rich working medium 13.
[0139] In addition to lithium hydroxide LiOH, this method also generates H 2 Hydrogen 2 Part of it is dissolved in the rich working medium 13 and is taken out from the second compartment 2 together with LiOH. In addition, the gaseous hydrogen H2 Accumulates in the battery.
[0140] Since hydrogen H 2 It is easy to degas from water, so it can be removed from the rich working medium without much effort. 2 When used as the second target product, a corresponding second separation device is provided, by which hydrogen (not shown) is obtained separately with appropriate quality / purity.
[0141] The water H present in the rich working medium 13 2 O is recycled as completely as possible as lean working medium 12. Only the water (crystallization water) present in the target product 15 is lost from the process. This must be replenished in the lean working medium 12 as required (not shown). The water in the feed 10 is not finally recycled between the second compartment 2 and the separation device 16, since the membrane 3 is impermeable to water. Example:
[0142] The present invention will now be described in detail with reference to experimental descriptions.
[0143] General experimental setup and procedures
[0144] To carry out the electrolysis, the electrolysis cell is first assembled and the anolyte and catholyte containers are connected. Care must be taken here to ensure that the inflow and return are connected in each case on the same side.
[0145] In one experimental design, both anode and cathode were described as planar electrodes. These consisted of titanium plates with a diameter of 19.5 mm and a thickness of 1.5 mm, coated on both sides with IrTi mixed oxide, 12 g Ir / m2 from Metakem GmbH, 61250 Usingen, Germany.
[0146] The sampled membranes were also discs with a diameter of about 25 mm. The thickness of the membranes was between 0.3 mm and 2 mm. The materials of the test membranes are specified in the individual examples.
[0147] The width b of the membrane perpendicular to the flow direction was in each case 14 mm. The specified width b is equal to the side length of a square whose perimeter has the same diameter as the circular active area A. The gap height h between anode and membrane was in each case 2.5 mm. In the case of using spacers, the gap height was reduced to 1.8 mm or 1.5 mm.
[0148] The electrolysis was blanketed with nitrogen throughout the process to prevent the formation of lithium carbonate. Each cell had a separate anolyte container and a separate catholyte container. Each container was filled with about 1 kg of liquid; the exact mass was determined by reweighing. The catholyte was always a 5 mmol / L LiOH solution. The anolyte was in each case a lithium salt solution of different concentrations and different lithium salts.
[0149] The experiment starts when the pump is switched on and the desired voltage is applied. The maximum flow rate is between 750 mL / min and 1000 mL / min, depending on how the individual experiments are set up. Samples are collected every half an hour or, by agreement, at longer time intervals. The first 3 ml of sample collected are discarded. For each sample collected, the power is recorded in each case and the conductivity of the sample is determined. The sample is then returned to a suitable container in order to keep the volume almost constant.
[0150] At the end of the experiment, the container was emptied and all leads as well as the membrane were rinsed with demineralized water. The cell was disassembled, the membrane was photographed, and SEM images of the catholyte and anolyte sides were recorded.
[0151] Membrane performance is measured by the parameter permeability (g Li*mm / m 2 *h) and permeance (g Li / m 2 *h). The permeability indicates how much mass of lithium is transported through the membrane per unit membrane area and per unit time. The permeability coefficient also takes into account the membrane thickness and therefore also makes it possible to compare different membrane types with different thicknesses to each other. In order to fully describe the performance, both are needed, because very thin membranes will allow very high permeabilities, but if there is a concentration polarization effect in the membrane cell, the permeability coefficient will not accurately reflect the actual situation. Considering the membrane thickness will no longer have any useful purpose, because the transmission will not be limited by the membrane.
[0152] All measured values shown in the examples are subject to a measurement error of approximately ±10% due to inaccuracies in the positioning of the electrodes relative to each other, inaccuracies in the thickness determination of the film samples, and inaccuracies in the concentration determination by conductivity measurement.
[0153] All ceramics used originated from the manufacturers listed in Table 0 and can be ordered from these sources under the corresponding product names.
[0154] Table 0: Ceramics used and their manufacturers
[0155]
[0156] The lithium hydroxide used was analytical grade lithium hydroxide from Aldrich. All other materials were technical grade.
[0157] Unless otherwise stated, LATSP films with a thickness of approximately 1 mm were used ( Ohara). The membrane plate is 100×10 5 Pa to 200×10 5 The membrane disks were produced by an SPS sintering process at a pressure of 250 Pa and a temperature of 950° C., or alternatively, membrane disks with dimensions suitable for the measuring cell were obtained directly from different manufacturers (Ohara, Ampcera, Toshima).
[0158] Description of the sintering process:
[0159] FAST / SPS sintering
[0160] The LATSP powder used is sintered by FAST / SPS (field assisted sintering technology / spark plasma sintering). Sintering is carried out under the condition of increasing pressure and temperature at the same time, so as to achieve high compaction and effective sintering in a very short sintering time. The sintering die assembly consists of a graphite die with an outer diameter of 80mm, an inner diameter of 36mm and a height of 55mm, two graphite half shells with a wall thickness of 10mm and the same height, and two graphite punches with a diameter of 25mm and a height of 30mm. The half shell is placed in the die, and a punch is introduced into the half shell from below. Before 2.5g of powder is weighed onto the lower punch in the die, a graphite foil is placed on the punch for better contact. After the powder is weighed, a second graphite foil is placed on the powder and an upper punch is introduced into the half shell. The die assembly is placed between two plates in the furnace chamber of the FAST / SPS furnace, each plate being made of carbon fiber reinforced graphite. The assembly is contacted via the path of travel of the electrode, and the desired pressure is accumulated. The mold is additionally heated by alternating current, which allows high temperatures to be reached in a short time. After gradually increasing the temperature to 250°C within five minutes, heating is continued at a rate of 130°C / min until a maximum temperature of 900°C is reached, which is maintained for a further five minutes. During the temperature increase, the pressure is also increased to 43 MPa within five minutes, which is likewise maintained for five minutes. At the end of the holding time, the upper electrode is disconnected from the mold and the mold is cooled. The sintered film can then be removed from the mold.
[0161] Example 1 (LATSP)
[0162] First, the voltage dependence of the ceramic membrane during electrolysis was studied. Electrolysis was performed with 0.1 mol / L LiOH and 1 mol / L LiOH at a voltage of 3 V to 6 V with a volume flow rate of 600 mL / min through the electrolytic cell. The results of the measurements are shown in Table 1.
[0163] In the graph of the values, the linear relationship is obvious. The intersection of the line with the x-axis at about 2V is due to the decomposition voltage of water and the internal resistance of the battery. The intersection points for these two concentrations are almost the same. The graph is shown in Figure 3 middle.
[0164] Table 1: Voltage dependence of ceramic membrane electrolysis
[0165]
[0166] Example 2 (LATSP)
[0167] It was also determined that the membrane performance was independent of the anolyte concentration. For this purpose, electrolysis was performed at voltages of 3 V and 6 V, with an initial charge of 0.1 mol / L, 1.0 mol / L, 2.0 mol / L or 4.0 mol / L of LiOH in the anolyte container in each case, and an anolyte volume flow rate of 600 mL / min through the electrolysis cell.
[0168] The molar proportion of LiOH corresponds to the following weight proportion of Li:
[0169] 0.1mol / L=700ppm Li=2400ppm LiOH
[0170] 1.0mol / L=7000ppm Li=24000ppm LiOH
[0171] 2.0mol / L=14 000ppm Li=48 000ppm LiOH
[0172] 4.0mol / L=28 000ppm Li=96 000ppm LiOH
[0173] The results of the measurements are shown in Table 2. At concentrations of 1 mol / L to 4 mol / L, the measured membrane performance did not improve significantly. A LiOH concentration of 0.1 mol / L achieved slightly lower performance. Figure 4 The results are shown in graphical form.
[0174] Table 2: Independence on anolyte concentration
[0175]
[0176] Example 3 (LATSP)
[0177] From the experimental results of Example 1 and Example 2, it can be seen that the permeability coefficient of lithium through the ceramic ion-conducting membrane is concentration-dependent, even though the driving force for the process is the applied voltage difference. In order to better describe this behavior, additional experiments were performed. These experiments were also performed over a larger voltage range between 3V and 15V. The volume flow rate through the anolyte compartment of the cell was 600mL / min, and anolyte concentrations of 0.1mol / L LiOH, 1.0mol / L LiOH, and 4.0mol / L LiOH were used.
[0178] The results of this study are summarized in Table 3.
[0179] Table 3: Relationship between permeability coefficient and voltage of LATSP
[0180]
[0181] Figure 5 The results are shown in graphical form.
[0182] From a certain voltage above 9 V, the permeability coefficient through the LATSP membrane used no longer increases further, but rather decreases significantly. Since 0.1 mol / L LiOH solution as anolyte appears to reach this limit at relatively low voltages and relatively low permeability coefficients, it is concluded that above this limit, there is an upper limit to lithium transport, which is caused by insufficient lithium transport at the membrane surface facing the anolyte side.
[0183] Example 4 (LAGP)
[0184] Example 3 was repeated with a different ceramic ion-conducting material (LAGP) with a material thickness of 0.3 mm, an anolyte concentration of 0.1 mol / L LiOH and an anolyte volume flow rate of 600 mL / min through the electrolytic cell, showing a similar picture. Here, too, above a certain limit, it was not possible to achieve a further increase in the permeability coefficient by increasing the voltage.
[0185] The results are summarized in Table 4.
[0186] Table 4: Relationship between permeability coefficient and LAGP voltage
[0187]
[0188]
[0189] Figure 6 The results are shown in graphical form.
[0190] Example 5 (LATSP)
[0191] When looking at the permeability, a series of experiments with 1.0 mol / L LiOH in the anolyte, a volume flow of 600 mL / min and different membrane thicknesses showed that the reason is the limited transport of lithium ions to the membrane surface on the anolyte side. In all experimental series, the region where a rise is no longer possible is between 60 and 75 g / m 2 ·h.
[0192] Therefore, for the given experimental setup, above this limit it is not possible to increase the lithium transport by increasing the voltage difference.
[0193] The results are summarized in Table 5.
[0194] Table 5: Permeability vs. voltage of LATSP
[0195]
[0196] Figure 7 The results are shown in graphical form.
[0197] Example 6 (LATSP)
[0198] When looking at the permeability and permeability coefficient, a series of experiments at 6 V with 1.0 mol / L LiOH in the anolyte, a volume flow of 600 mL / min, and membranes of varying thicknesses show that up to a membrane thickness of 0.75 mm, these show the expected relationship to each other via the membrane thickness. For thinner membranes, both deviate from the expected behavior to lower values, at Figure 8 The values are shown in Table 6.
[0199] Table 6: Relationship between permeability and permeability coefficient and membrane thickness
[0200]
[0201] Figure 8 The results are shown in graphical form.
[0202] Each of Examples 1 to 6 shows that the technically desired high lithium permeability cannot be achieved by thin films or high voltages alone, nor by selecting a ceramic with the best possible Li conductivity, but that further measures are required to achieve this.
[0203] Example 7 (LATSP)
[0204] In electrolysis experiments carried out at a voltage of 3 V and various volume flow rates with 0.1 mol / L and 1.0 mol / L LiOH solutions as anolyte, it has been previously observed that the transport of lithium through the membrane depends on the volume flow rate and therefore also on the cross-flow velocity, even at low permeabilities.
[0205] The results are summarized in Table 7.
[0206] Table 7: Dependence of permeability of LATSP on volume flow rate
[0207]
[0208] Fig. 9 The results are shown in graphical form.
[0209] Example 9 (LAGP)
[0210] These results show that, surprisingly, even at very low voltages and permeabilities, the access of lithium from the flow to the membrane surface has a significant impact on the overall performance of the process. Access to the surface is controlled by the cross-flow velocity at the membrane surface and therefore by the volume flow through the anolyte cell.
[0211] Further increases in volumetric flow at a voltage of 6 V and an anolyte concentration of 1.0 mol / L LiOH showed that this allowed lithium transport (permeability) to increase beyond the previously observed limit to greater than 110 g / L. Li / m 2 ·h.
[0212] The results are summarized in Table 8.
[0213] Table 8: Dependence of LAGP permeability on volume flow rate
[0214]
[0215] Fig.10 The results are shown in graphical form.
[0216] Example 10 (LAGP)
[0217] A further increase in the volume flow rate at a voltage of 6 V and an anolyte concentration of 1.0 mol / L LiOH could not be achieved by the device settings. Therefore, as a further measure, the use of alternative electrode geometries and separator materials was examined.
[0218] Spacers are available from the following companies:
[0219] Fine spacer (72% open area)
[0220] SWM; 601 Industrial Drive, Middletown, DE 19709, USA
[0221] Model Naltex N02016_90PP
[0222] Coarse spacer (55% open area)
[0223] Intermas Nets SA
[0224] Ronda Collsabadell,11,08450Llinars del Vallès(Barcelona),Spain
[0225] The installation of the thin spacers reduces the gap height from 2.5 mm to 1.8 mm, while the thick spacers reduce the gap height to 1.5 mm. By installing the spacers, the membrane width of 14 mm remains unchanged.
[0226] The results of the studies conducted at volume flow rates of 70 to 750 mL / min, 6 V, and 1 mol / L LiOH solution are shown in Table 9.
[0227] In all arrangements, an increase in volume flow leads to an increase in lithium transport through the membrane. From the results it can be seen that at a voltage of 6 V, the transport depends on the electrode area and the open accessible area of the membrane (the area not covered by the bars of the spacer). The increase in permeability caused by the introduction of the spacer is not noticeable, its purpose is to ensure greater mixing of the feed volume flow.
[0228] The trends in the permeability show that these converge in all process types at volume flows in the anolyte compartment of about 1000 mL / min and above. It can therefore be assumed that above this volume flow it is only transported through the rate-determining ceramic lithium ion conducting membrane.
[0229] Table 9: Effect of spacers on cross flow velocity and permeability
[0230]
[0231] Fig.11 A graph of measured permeability versus volume flow rate is shown.
[0232] Example 11 (LAGP)
[0233] At a volume flow rate of 1000 mL / min, the voltage was increased in stages. In this experiment, it was found that the coarse spacer geometry (55% open porosity) employed ensured that the feed containing 1.0 mol / L LiOH was well mixed, and the voltage was increased to achieve greater than 300 g without exceeding 15 V. Li / m 2 h, above which even higher voltages result in a known permeability drop.
[0234] Experiments attempting to achieve this using planar electrodes without spacers at the same volume flow rate produced similar results at the high voltages studied.
[0235] Fig.12 The permeability versus voltage is shown with spacers (▲) and without spacers (O). The values are presented in Table 10.
[0236] Table 10: Effect of spacer and voltage on permeability
[0237]
[0238] It has thus been shown that establishing the highest possible cross-flow velocity / volume flow rate allows the permeability of the LiSICon membrane used in membrane electrolysis to be significantly increased to a certain extent, making economic use possible. Surprisingly, the spacers usually used between the polymer ion exchange membrane and the electrodes in membrane electrolysis are not necessary, because the ceramic membrane is dimensionally stable during use and thus keeps the defined flow channels open. The use of spacers in combination with ceramic membranes is then less desirable, because the bars of the polymer spacer block part of the exchange area.
[0239] Example 12 (LAGP)
[0240] When using a planar electrode, Experiment 11 was repeated using only an anolyte solution having a concentration of 0.1 mol / L LiOH. The results are shown in Tables 11 and Fig.13 In the figure, it is represented by the “□” data point.
[0241] Table 11: Effect of voltage on permeability
[0242]
[0243] In this case, the permeability can also be increased by increasing the voltage. However, as previously shown in Example 11, above a certain limit, any further increase in permeability is not possible, and increasing the voltage further results in a decrease in permeability. This permeability limit is lower than the limit when using a 1.0 mol / L solution as shown in Example 11 (see "O" data point), but is more than twice higher than the comparative experiment with a lower cross-flow velocity.
[0244] It has been demonstrated that establishing the highest possible cross-flow velocity / volume flow rate allows the permeability of the LiSICon membrane used in membrane electrolysis to be significantly increased to a certain extent, making economical use possible.
[0245] Reference numerals list
[0246] 0 Electrochemical Cell
[0247] 1 First compartment
[0248] 2 Second compartment
[0249] 3 Membrane
[0250] 4 Anode
[0251] 5 Cathode
[0252] 6 First electrical lead
[0253] 7 Voltage Source
[0254] 8 Second electrical lead
[0255] 9 Unspecified
[0256] 10 Feed
[0257] 11 Unspecified
[0258] 12 Lean working medium
[0259] 13 Rich working medium
[0260] 14 Wastewater
[0261] 15 Target product
[0262] 16 Separation equipment
[0263] H 2 O water
[0264] H 2 hydrogen
[0265] O 2 oxygen
[0266] LiOH Lithium Hydroxide
[0267] OH - OH anion
[0268] Li + Lithium cation
[0269] U Voltage
[0270] I Current
[0271] A Effective area
[0272] C F LiOH concentration in feed
[0273] C W LiOH concentration in wastewater
[0274] C M0 LiOH concentration in lean working medium
[0275] C M1 LiOH concentration in rich working medium
[0276] b Width of the membrane perpendicular to the flow direction
[0277] h is the height of the gap between the membrane and the anode
[0278] Q Volume flow rate through the first compartment
[0279] CFV Cross Flow Velocity
Claims
1. A method for producing hydrogen and lithium hydroxide, comprising the following steps: a) providing a feed comprising at least water, Li ions and impurities, wherein the concentration of Li ions in the feed is C F at least 200 ppm by weight or between 500 ppm by weight and 140 000 ppm by weight, in each case based on the total weight of the feed, b) providing a lean working medium comprising water and lithium hydroxide dissolved therein, wherein the concentration of lithium hydroxide in the lean working medium is C based on the total weight of the lean working medium. M0 At least 50 ppm by weight; c) providing at least one electrochemical cell, wherein the electrochemical cell has the following characteristics: v. The electrochemical cell comprises a first compartment in which an anode is arranged; vi. The electrochemical cell comprises a second compartment in which a cathode is disposed; vii. the electrochemical cell comprises a flat membrane separating the first compartment from the second compartment, The flat membrane has an area A; viii. the flat membrane comprises an inorganic material having Li ion conductivity, and is electrically insulating; d) providing at least one voltage source connected to the anode via a first electrical lead and to the cathode via a second electrical lead; e) continuously filling the first compartment with the feed; f) filling the second compartment with the lean working medium; g) charging the electrochemical cell with a voltage U taken from the voltage source so that a current I flows between the anode and the cathode, and a ratio Q of the current intensity of the current I to the area A of the flat membrane is between 100 A / m 2 and 500A / m 2 Between or 150A / m 2 and 350A / m 2 between; h) continuously taking out wastewater containing at least water, Li salt dissolved therein, oxygen and impurities from the first compartment, wherein the concentration of Li ions in the wastewater is C based on the total weight of the wastewater. W Lower than the concentration of Li ions in the feed C F ; i) taking out a rich working medium containing water, lithium hydroxide and hydrogen from the second compartment, wherein the concentration of lithium hydroxide in the rich working medium is C based on the total weight of the rich working medium. M1 Greater than the concentration C of lithium hydroxide in the lean working medium M0 , In which, due to the continuous filling of the first compartment with the feed and the continuous withdrawal of wastewater from the first compartment, a first flow is formed, and the first flow flows through the first compartment along the flat membrane at a cross-flow velocity CFV, and the cross-flow velocity CFV is greater than 220 mm / s or greater than 350 mm / s or greater than 470 mm / s.
2. The method according to claim 1, characterized in that The cross flow velocity CFV is lower than a critical velocity, which is selected from the following critical velocities: 600 mm / s, 960 mm / s, 1500 mm / s, 2400 mm / s, 3780 mm / s and 6000 mm / s.
3. The method according to claim 1 or 2, characterized in that: The first compartment is free of flow internals.
4. The method according to claim 3, characterized in that The first compartment has no partition.
5. The method according to any one of claims 1 to 4, characterized in that The flat sheet membranes are assembled in flat sheet modules.
6. The method according to any one of claims 1 to 5, characterized in that The feed contains anions selected from sulfate, carbonate, hydroxide and chloride.
7. The method according to any one of claims 1 to 6, characterized in that The feed contains impurities in the form of compounds of elements selected from the group consisting of B, Na, Mg, Al, Si, K, Ca, Mn, Fe, Co, Ni, Cu and C.
8. A method according to any one of the preceding claims, wherein the conductivity of the inorganic material present in the flat membrane to Li ions, measured by the "impedance spectroscopy" method described herein, is at least 1×10 -5 S / m or at least 5×10 -5 S / m or at least 10×10 -5 S / m, and not more than 100×10 -5 S / m.
9. The method according to claim 8, characterized in that The inorganic material is a compound with the following stoichiometry (LATP): Li 1+x Al x Ti 2-x (PO4)3 Wherein: 0.1≤x≤0.3, wherein preferably x=0.
3.
10. The method according to claim 8, characterized in that The inorganic material is a compound with the following stoichiometry (LATSP): There 1+x+y To the x You 2-x Yes y P 3-y OR 12 Among them: 0.1≤x≤0.3 and 0.2≤y≤0.
4.
11. The method according to claim 8, characterized in that The inorganic material is a compound with the following stoichiometry (LAGTSP): The 1+x+y Al x Ti 2-x If y P 3-y O 12 *nGeO2 Among them: 0≤x≤1 and 0≤y≤1 and 0≤n≤1.
12. The method according to claim 8, characterized in that The inorganic material is a compound with the following stoichiometry (LAGTP): Li 1.4 Al 0.4 (Ge 1-x Ti x ) 1.6 (PO4)3 Among them: 0≤x≤1.
13. The method according to claim 8, characterized in that The inorganic material is a compound (LAGP) having the following stoichiometry: <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> 1+x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> Ge<h2 style=";text-align:left;direction:ltr"> 2-x <h2 style=";text-align:left;direction:ltr"> (PO4)3 Where: x=0 or x=0.2 or x=0.
4.
14. The method according to claim 8, characterized in that The inorganic material is a compound having the following stoichiometry (LLTO): He 3x The (2 / 3)-x□(1 / 3)-2x TiO3 Where: 0≤x≤0.
16.
15. The method according to any one of claims 9 to 14, characterized in that The flat sheet membrane is entirely composed of the inorganic material.
Citation Information
Patent Citations
Processes for preparing lithium hydroxide
EP3805428A1
Processes and systems for preparing lithium hydroxide
US10036094B2
Metal ion recovery device and metal ion recovery method
US20160201163A1
Device and method for recovery or extraction of lithium
US9222148B2
Systems and methods for selectively extracting alkaline metals from metal-rich solutions using solid state ionic conductive electrolyte membrane
WO2019055730A1